Sinden-Pangreman Staging Style in Wayang Jek Dong Performance of Pandhawa Laras Group - Tosabila, Inggar Belzky; Sekti, Retnayu Prasetyanti (MSJ : Majority Science Journal, 2024)
Pandhawa Laras is a group engaged in the field of performing arts, especially East Javanese shadow puppetry (Jek Dong), which was founded on May 13, 2009. Pandhawa Laras means Pan "Panjak," Dha "Dalang,” and Wa "Waranggana,” and Laras means that these three aspects become a unity in a harmonious performance. Pandhawa Laras was founded when there was already an existence of Remo dance, both male Remo dance and female Remo dance, in shadow puppet shows. Through the years, the female Remo dance has shifted to the male Remo dance. The male Remo dance in the Jek Dong puppet show of the Pandhawa Laras group is danced by Sinden (Pangreman) with male-like makeup. This research will discuss the staging style of Sinden-Pangreman. The study of this research leads to the theory of staging style with a descriptive qualitative approach. By utilizing data collection techniques such as observation, interviews with relevant sources, literature study, and documentation, Furthermore, data analysis is carried out through data reduction, data presentation, and finally drawing conclusions or verifying valid data. Based on the research results of the Sinden-Pangreman staging style in the Jek Dong puppet show of Pandhawa Laras Group, the men's Remo dance in the Jek Dong puppet show is performed during the pre-event by the puppet Sinden, who also acts as Pangreman. This is evidenced by the presence of two wayang kulit Sinden who, before climbing the puppet stage, will dance the Remo putra dance in the Malangan style. The performance is accompanied by two kidungan sessions, with the second kidungan referred to as Kidungan Jula-juli. This research shows that in the Sinden-Pangreman staging style there are supporting elements in the actors in performing the Remo putra dance and as a wayang kulit sinden, including dance movement, dance style, kidungan, makeup, and the interaction process in the performance.